Complete Resection of a Large Mediastinal Calcifying Fibrous Tumor - Géraldine L. P. Bono; Markus Lehner; Freimut H. Schilling; Nikolai Stahr; Miriam Nowack; Philipp O. Szavay (Georg Thieme Verlag KG, 2020)
Calcifying fibrous tumor (CFT) is a benign tumor entity which can present in a variety of different sites. Till date, eight cases with a mediastinal manifestation have been published in literature. Surgical removal is the treatment of choice for this often incidentally detected tumor. Surgery of thoracic CFT may be challenging due to its localization within the mediastinum. A 10-year old boy with a right-sided thoracic pectus carinatum-like deformity was referred for further evaluation, incidentally, revealing a mediastinal mass in computed tomography (CT). Laboratory results were all within normal range. Magnetic resonance imaging (MRI) showed a large tumor in the upper anterior mediastinum suggesting expansive but not infiltrative character. The tumor was displacing surrounding structures like the heart and the diaphragm. Lower venous stasis with dilation of the inferior cava vein could be demonstrated. The tumor was considered to be of benign dignity and surgical removal was indicated. Complete tumor resection could be achieved through a sternotomy approach, along with thymectomy. A partial resection of both the pericardium and diaphragm was required due to adhesion with soft tissue at those sites. The specimen's size was 320 mm × 145 mm × 100 mm, histologically confirmed as CFT. The patient showed no residual tumor at 3- and 9-month follow-up. This case is a report on a large mediastinal CFT which underwent successful complete surgical removal. Following tumor resection, prognosis is considered to be good; however, key issue is complete resection to avoid local tumor recurrence.